2015
DOI: 10.1007/s12274-014-0697-3
|View full text |Cite
|
Sign up to set email alerts
|

How toxic are gold nanoparticles? The state-of-the-art

Abstract: With the growing interest in the applications of gold nanoparticles in biotechnology and their physiological effects, possible toxicity of gold nanoparticles is becoming an increasingly important issue. A large number of studies carried out over the past few years under a variety of experimental conditions and following different protocols have produced conflicting results, leading to divergent views about the actual safety of gold nanoparticles in human applications.This work is intended to provide an overvie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
200
0
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 270 publications
(217 citation statements)
references
References 147 publications
3
200
0
5
Order By: Relevance
“…In the LNCaP cell line, AuNPs-PEGTf, AuNPs-PEI and AuNPs-PEI-FA displayed IC50 values of 103, 118 and 110 μg mL −1 respectively. Similar data were also observed in PC-3 cells, with IC50 values of 107, has been reported that toxicity of AuNPs is dependent on particle size, surface charge, morphology, surface chemistry, ligand types and the mechanisms of cellular uptake [29].…”
Section: Cytotoxicitysupporting
confidence: 87%
“…In the LNCaP cell line, AuNPs-PEGTf, AuNPs-PEI and AuNPs-PEI-FA displayed IC50 values of 103, 118 and 110 μg mL −1 respectively. Similar data were also observed in PC-3 cells, with IC50 values of 107, has been reported that toxicity of AuNPs is dependent on particle size, surface charge, morphology, surface chemistry, ligand types and the mechanisms of cellular uptake [29].…”
Section: Cytotoxicitysupporting
confidence: 87%
“…Gold nanoparticles potentially outperform other physical techniques by offering high efficiency, viability, and throughput [21,28,29]. However, nanoparticles are sometimes ingested into the cell, which can have unwanted side effects at high concentrations [17,20,[30][31][32]. Plasmonic substrate-based methods operate with the same physical poration mechanism as plasmonic nanoparticles but use lithography techniques to precisely pattern a surface of nanostructures that are not ingested by the cell.…”
Section: Introductionmentioning
confidence: 99%
“…52,54,55 However, the relatively inert AuNPs with appropriate coating are thought to have no side effects on human health. [56][57][58] Moreover, the AuNPs used in the present study were obtained from the nonpathogenic bacterium D. radiodurans, and the antibacterial activities of these AuNPs have potential biomedical applications.…”
mentioning
confidence: 99%